Potensi Sapi Lokal Dalam Upaya Mewujudkan Kecukupan Daging Dan Pengembangan Kawasan Peternakan - A. Agustar; Jaswandi Jaswandi (Universitas Andalas, 2006)
The present paper discussed the contribution of animal production on protein consumption of the people of Indonesia. The quite protein intake is mainly caused the limited sources of food protein, which was indicated by relatively high price of animal praduct for food. In the contrary, Indonesia have many kinds indegineuous livestock animals, which have became a part of socio-economic live of the people, like Bali and Pesisir cattle.